A proposed mechanism to explain increases in intracranial pressure: The concept of cerebral artery wedge pressure - Hamilton, DR; Mitha, A; Hamilton, MG; Tyberg, JV (Journal of Cardiology and Cardiovascular Medicine, 2020)
We hypothesize that, with elevated cerebral spinal fluid (CSF) pressure, cerebral micro-vascular obstruction and congestion may occur despite (subdural) large-vein pressures being normal. Smaller veins emptying into these larger, dura-enveloped veins are not immune to the compressive effects of elevated CSF pressure and a “Starling Resistor” mechanism might explain why elevated CSF pressures collapse these smaller veins. This small cerebral venous starling resistor compression mechanism may be the final common pathway for many patients suffering from increased CSF pressures and might also be an important contributor to impaired focal venous drainage presenting as a headache with normal venous sinus pressures.